2018
DOI: 10.1038/s41440-018-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstructive sleep apnea on long-term blood pressure variability in Japanese men: a cross-sectional study of a work-site population

Abstract: Blood pressure variability (BPV) has been shown to be associated with cardiovascular diseases. The effects on long-term BPV of obstructive sleep apnea (OSA) are not yet known. We evaluated a total of 1653 Japanese male workers (18-69 years) at a work site to diagnose OSA, and we divided them into three groups: non-OSA (apnea-hypopnea index (AHI): < 5, n = 1414), mild-to-moderate OSA (5 ≤ AHI < 30: n = 131) and severe OSA (AHI ≥ 30: n = 108). The standard deviation and coefficient of variation of the subjects' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…30 Existing studies were mainly focused on the association of BPV with sleep-disordered breathing, suggesting the possible contribution of OSA to increased visit-to-visit BPV. 31,32 In this context, we hypothesized that increased visit-to-visit BPV, an indicator of subclinical CVD, could be associated with poor sleep quality independent of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…30 Existing studies were mainly focused on the association of BPV with sleep-disordered breathing, suggesting the possible contribution of OSA to increased visit-to-visit BPV. 31,32 In this context, we hypothesized that increased visit-to-visit BPV, an indicator of subclinical CVD, could be associated with poor sleep quality independent of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the impact of sleepdisordered breathing, including insomnia and sleep apnea, could not be evaluated because we could not monitor sleepdisordered breathing. Sleep-disorder breathing has been shown to be related to hypertension [21,24] or blood pressure variability [25], and a nondipping pattern in normotensive patients with obstructive sleep apnea may progress to carotid atherosclerosis [26]. Our findings may partially represent the relationship between sleep-disordered breathing and hypertension.…”
Section: Discussionmentioning
confidence: 56%
“…Several previous studies identified associations between BP variability and OSA in adults 61–65 . Martynowicz reported higher nocturnal SBP variability and DBP variability in patients with severe OSA compared with those with mild‐to‐moderate OSA 62 .…”
Section: Discussionmentioning
confidence: 95%